2005
DOI: 10.1177/104990910502200206
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care volunteerism among college students in Canada

Abstract: The goal of Study 1 was to investigate whether young Canadian adults were interested in becoming involved in palliative care volunteer work. After reading a brief description of what volunteering in a palliative care environment typically involves, participants (undergraduate students) were asked to indicate whether they would be interested in this kind of volunteer experience and to provide a written explanation of their answer. Of the 105 participating students, only 39 (37.1 percent) expressed an interest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
3
12
0
Order By: Relevance
“…Every fourth middle-aged or older male shopper was approached by a researcher and asked whether he could spare a few minutes to complete a questionnaire. The questionnaire used in this study was similar to the one employed by ClaxtonOldfield et al 8 It contained a brief description of the kinds of tasks hospice palliative care volunteers typically perform, constructed, in part, from Kastenbaum's 14 description of what volunteers do. It read as follows:…”
Section: Study 1 Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Every fourth middle-aged or older male shopper was approached by a researcher and asked whether he could spare a few minutes to complete a questionnaire. The questionnaire used in this study was similar to the one employed by ClaxtonOldfield et al 8 It contained a brief description of the kinds of tasks hospice palliative care volunteers typically perform, constructed, in part, from Kastenbaum's 14 description of what volunteers do. It read as follows:…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…The most common reason students gave for wanting to become a palliative care volunteer was ''the desire to help others''; the most common reason given for not wanting to do this kind of volunteer work was that it would be ''too emotionally demanding or draining'' (eg, many of the students felt that they would not have the strength emotionally to be with someone they knew was going to die). Although students of Claxton-Oldfield et al 8 were not interested in working with the dying, the results of study 2 revealed that many young people are interested in volunteering in a food bank, classroom, or nursing home. On a side note, it seems that when young people do become involved in palliative care, they find the experience very rewarding.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…8,29,36,38,39 Across the 2 age-groups, the 4 most salient motives for volunteering were values, understanding, social bonding, and enhancement. Weak support was found for some assumptions regarding the socioemotional selectivity theory, 40 which suggests that as individuals age, they experience a shift in priorities of their social goals emphasizing goals related to emotional gratification, while social goals related to knowledge seeking become less important.…”
Section: Impact Of Age On Motivation To Volunteermentioning
confidence: 99%
“…5 Those who choose this form of participation do so deliberately, based on a strong desire to help in this particular domain of service. 6,7 The presence of volunteers in palliative care assists not only patients and their families but also the staff.…”
mentioning
confidence: 99%